Pemanfaatan Kulit Bawang Sebagai Pestisida Nabati Untuk Menghambat Hama Kutu Daun Dan Ulat Grayak: pemanfaatan kulit bawang menjadi pestisida nabati - salda; Marlia Rianti; Fatmawati Ramli; Taslim (Universitas Mataram, 2024)
This service aims to use shallot skins as a vegetable pesticide to control aphids and armyworms in Pekalobean Village, Anggeraja District, Enrekang Regency, South Sulawesi. The methods used include outreach and training in making vegetable pesticides to local communities. The process of making this pesticide uses natural ingredients such as shallot skins, lemongrass stems and soursop leaves which are easy to obtain and not harmful to the environment. The results of this activity show that the community can understand and practice making plant-based pesticides, so it is hoped that they can reduce dependence on chemical pesticides. This activity not only provides new knowledge but also contributes to reducing onion skin waste. In conclusion, the use of botanical pesticides made from shallot skins is an effective and environmentally friendly solution for sustainable agriculture